2020
DOI: 10.1200/po.19.00292
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Predicts the Response and Prognosis in Patients With Early Breast Cancer Receiving Neoadjuvant Chemotherapy

Abstract: PURPOSE Many patients with breast cancer still relapse after curative treatment. How to identify the ones with high relapse risk remains a critical problem. Circulating tumor DNA (ctDNA) has recently become a promising marker to monitor tumor burden. Whether ctDNA can be used to predict the response and prognosis in patients with breast cancer receiving neoadjuvant chemotherapy (NAC) is unknown. Our study aimed to evaluate the clinical value of the presence and dynamic change of ctDNA to predict the tumor resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
4
25
0
1
Order By: Relevance
“…Our pre-NAC ctDNA detection rate of 77% was comparable with the published literature. [12][13][14][15] The post-NAC detection rate of 43.4% was, however, higher and likely reflects the fact that we had several patients with large primary tumor size and positive nodal status at initial presentation, which also justifies the low rate (13%) of pCR reported.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our pre-NAC ctDNA detection rate of 77% was comparable with the published literature. [12][13][14][15] The post-NAC detection rate of 43.4% was, however, higher and likely reflects the fact that we had several patients with large primary tumor size and positive nodal status at initial presentation, which also justifies the low rate (13%) of pCR reported.…”
Section: Discussionmentioning
confidence: 87%
“…11 By comparison, ctDNA is detected in 57%-100% of patients with non-metastatic BC, suggesting it may represent a more broadly applicable biomarker in this setting. [12][13][14][15] Intriguingly, studies suggest that residual ctDNA after curative-intent surgery of localized BC is a valuable marker in patients at the highest risk of recurrence. Minimal residual disease can be detected shortly after treatment, and ctDNA changes after treatment may be predictive of long-term outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous smaller studies have explored the question of how the detection of circulating DNA may complement treatment monitoring in early breast cancer ( Table 5 ). Li et al studied plasma samples before, during and after neoadjuvant chemotherapy in 52 patients and demonstrated that ctDNA analysis after 2 cycles of treatment correlated better with pCR probability than radiological diagnostic work-up 34 . Similar results were reported by Magbanua et al, who performed ctDNA ultra-deep sequencing in 84 patients treated in the I-SPY 2 trial 35 .…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancementioning
confidence: 99%
“…5 ). Li et al untersuchten Plasmaproben vor, während und nach der neoadjuvanten Chemotherapie bei 52 Patientinnen und konnten zeigen, dass die Bestimmung der ctDNA nach 2 Zyklen der Therapie mit der pCR-Wahrscheinlichkeit besser korreliert als die radiologische Diagnostik 34 . Ähnliche Ergebnisse wurden von Magbanua et al berichtet, die ctDNA mittels Ultra-deep Sequencing bei 84 im Rahmen der I-SPY 2-Studie behandelten Patientinnen untersuchten 35 .…”
Section: Therapiemonitoring Mittels Liquid Biopsyunclassified
“…Thus, recurrence with distant metastasis is observed, although infrequently, even after the administration of standard treatment according to the tumor subtype and pathological stage. Several studies have demonstrated that the level of circulating tumor DNA, detected by liquid biopsy, is related to efficacy and prognosis for metastatic breast cancer treated with anticancer agents and early-stage breast cancer treated with neoadjuvant chemotherapy (NAC) (19)(20)(21), but no such assessment method is available for adjuvant therapy. As breast cancer is a systemic disease, residual or circulating tumor cells may be present after surgical treatment.…”
mentioning
confidence: 99%